Science Symposiums: Connecting Scientists, Managers, and Citizens - Alyssa R. Dodd; Jo Anne Jolley; Mark A. Brennan (EDIS)
FCS9261, a 9–page fact sheet by Alyssa R. Dodd, Jo Anne Jolley, and Mark A. Brennan, proposes that public natural resource science symposiums can serve an important function, uniting and educating scientists, managers, and citizens, and helping to guide research. Using examples from their experience planning the Loxahatchee River Watershed Science Symposiums, the authors provide specific guidance on planning and carrying out such a symposium. Published by the UF Department of Family, Youth and Community Sciences, January 2007.